End-to-end low cost space missions beyond earth orbit : a case study for the moon - Jason, S. (Cranfield University, 2001)
The research project describes the key mission and systems engineering trade-offs involved in the end-to-end design of an orbiting mission to the Moon, using a "Smaller, Faster, Cheaper" mission approach. This approach is extended to enable the design of a new payload - within the management, cost, schedule, and physical constraints - of the low cost lunar orbiter mission. The payload is designed to image the Moon's permanently dark regions that are believed to contain water ice. To determine the best cost reduction management and engineering approach, the principles for reducing space mission cost are examined and planetary missions are assessed in terms of cost and risk drivers. 'Interplanetary' trajectories and attaining orbit around another body are shown to be the major risk areas encountered by traditional planetary missions. In addition to this, programme management is highlighted as an emerging high risk area for smaller, faster cheaper planetary missions. The preliminary mission design, covering lunar transfer, spacecraft and ground station is described. A 400 kg, three-axis stabilised, lunar orbiter, capable of delivering 20 kg of payload into a low lunar polar orbit is designed. The ground segment comprises one (possibly two) low cost ground stations, linked via the Internet. Images, raw data and telemetry can also be accessed via the Internet. The design-to-launch timeframe spans three years and the total mission cost target of $20 Million is met. The spacecraft is compatible with a range of existing lunar payloads, but the prime mission requirement will be to return images of the Moon's permanently dark craters for the first time. In order to design a low cost payload for imaging the Moon's permanently dark regions, the areas likely to contain the water ice are first characterised. The best and worst case lighting conditions for imaging are then calculated for these regions. The amount of light reaching a crater floor is a function of the crater depth-diameter ratio, solar irradiance incidence angle and local topography. The limiting case is shown to be imaging under starlight illumination only, which is modelled and estimated between 5 to 10µW/m2 over the 350 to 900 nm spectral band. These ultra-low light level conditions have led to identification and evaluation of several solutions in terms of both signal-tonoise ratio performance and development within the constraints of the smaller, faster, cheaper programme. This is achieved using a charge coupled device (CCD) camera employing a commercial sensor and optics. Large format Charge Injection Devices and Complimentary Metal Oxide Semiconductors (Active Pixel Devices) were identified as promising emerging technologies. The baseline low light level imager solution is a CCD array operated in Time Delay Integration mode in order to provide optical images from areas within permanent shadow. An intensified CCD offers a back up solution. The research demonstrates that a low cost lunar mission is technically feasible and additionally, that it is possible to meet a specific (if modest) application target through `smaller, faster, cheaper' payload design. It provides an approach that meets key challenges of planetary exploration at very low cost that can potentially be applied to other near Earth targets.